Effects of Kindergarten, Family Environment, and Physical Activity on Children's Physical Fitness - Huang, Wenyan; Luo, Jiong; Chen, Yanmei (Frontiers in Public Health, 2022)
In order to explore the relationship between kindergarten environmental factors, children's physical activity and healthy physical fitness, this study uses the stratified random sampling method to obtain 4600 children in relevant kindergartens. The questionnaire survey and children's physical fitness test were completed with the help of parents and kindergarten staff. The combination of exploratory (EFA) and confirmatory (CFA) factor analysis is used to process the obtained database and set the significance level of all indicators α= 0.05. The results show that kindergarten environmental factors significantly affect children's physical activity and healthy physical fitness. Children with large play area in these kindergartens , more sports equipment items, more than 3 games per week, no less than 40 minutes of each class, appropriate number of classes and excellent teachers' teaching ability who have better healthy physical fitness. Family environmental factors significantly affect children's physical activity and health fitness. Children with more family sports equipment items, more peers living nearby, safer playing places, more hands and feet and parents who are good at sports have better performance in health fitness. Children's physical activity not only directly affects their performance of healthy physical fitness, but also plays a dual intermediary role between kindergarten environment and healthy physical fitness, family environment and healthy physical fitness.